Mule/Huwe1/Arf-BP1 suppresses Ras-driven tumorigenesis by preventing c-Myc/Miz1-mediated down-regulation of p21 and p15 - Inoue, Satoshi (Cold Spring Harbor Laboratory Press, 2013)
Tumorigenesis results from dysregulation of oncogenes and tumor suppressors that influence cellular proliferation, differentiation, apoptosis, and/or senescence. Many gene products involved in these processes are substrates of the E3 ubiquitin ligase Mule/Huwe1/Arf-BP1 (Mule), but whether Mule acts as an oncogene or tumor suppressor in vivo remains controversial. We generated K14Cre;Mule(flox/flox(y)) (Mule kKO) mice and subjected them to DMBA/PMA-induced skin carcinogenesis, which depends on oncogenic Ras signaling. Mule deficiency resulted in increased penetrance, number, and severity of skin tumors, which could be reversed by concomitant genetic knockout of c-Myc but not by knockout of p53 or p19Arf. Notably, in the absence of Mule, c-Myc/Miz1 transcriptional complexes accumulated, and levels of p21CDKN1A (p21) and p15INK4B (p15) were down-regulated. In vitro, Mule-deficient primary keratinocytes exhibited increased proliferation that could be reversed by Miz1 knockdown. Transfer of Mule-deficient transformed cells to nude mice resulted in enhanced tumor growth that again could be abrogated by Miz1 knockdown. Our data demonstrate in vivo that Mule suppresses Ras-mediated tumorigenesis by preventing an accumulation of c-Myc/Miz1 complexes that mediates p21 and p15 down-regulation.